Determinants of quality of headquarters-subsidiary relationship: A study of Chinese multinational enterprises - Li, Jizhong (Curtin University, 2014)
Based on the institutional, social exchange, and upper echelons theories, this thesis develops a theoretical framework and examines the factors affecting the quality of headquarters-subsidiary relationship of Chinese multinational enterprises (MNEs). Hypotheses were tested using survey data collected from both headquarters and subsidiaries of 354 Chinese MNEs. Data analysis results and findings are presented in the thesis, and the theoretical contributions and practical implications are also discussed.